The elusive climate migrant: symbolic geographies in migration studies - Víctor Pérez-Segura; Raquel Caro-Carretero; Antonio Rua (Comparative Migration Studies)
Abstract Climate migration has emerged as one of the fastest-growing lines of inquiry within migration studies. However, it suffers from a fundamental empirical–conceptual limitation: the absence of a definition that clearly distinguishes a climate migrant from a labour migrant. This research aims to determine how the specialised literature positions the phenomenon, which forms of mobility it recognises and the extent to which the geographical context of scientific production influences its territorial delineation. To this end, the territorial location of migrant populations was analysed in a sample of 1,059 articles drawn from the WoS, Scopus and LENS databases. The results indicate that 39% of the studies treat the phenomenon in a decontextualised manner — without linking it to specific populations or migration processes. When territories are mentioned, 27% of the references pertain to Bangladesh and the Pacific islands. It is also observed that territorial identification is conditioned by the country of production, which tends to situate the phenomenon in spaces with which it has pre-existing migratory, geographical or historical ties. These findings are discussed from the perspectives of Science and Technology Studies (STS), the Geography of Science and decolonial thought. It is concluded that research on climate migration reproduces the epistemological positions of the Global North — the main generator of knowledge in this field. This produces a symbolic territorialisation of the phenomenon guided by securitising frameworks and a tendency to prioritise climate as the decisive factor.